PENGEMBANGAN KOMODITI SUBSEKTOR TANAMAN PERKEBUNAN DAN PETERNAKAN KAWASAN ANDALAN KABUPATEN BULUKUMBA PROVINSI SULAWESI SELATAN - -, Rusida (Jurnal Ilmiah Ecosystem, 2020)
The purpose of this study was to determine the types of superior commodities in the estate crops subsector and livestock subsector which are the base sector in the Mainstay Area of Bulukumba Regency, South Sulawesi Province. The research method used is observation, the data analyzed are secondary data. Data was collected from several sources such as: the Central Statistics Agency of the Regency of Bulukumba, the Regional Development Planning Agency of the Regency of Bulukumba, the Office of Food Crops, Horticulture and Plantation of the Regency of Bulukumba. Regional analysis methods used are the LQ Analysis Method and the Locality Analysis The results of the analysis show that in the Mainstay Area of Bulukumba Regency there are: (i) six sub-districts which are very superior for the plantation sub-sector of coconut commodities, three sub-districts for rubber commodity, three sub-districts for coffee commodity, five subdistricts for cacao commodity, four sub-districts for clove commodity and two sub-districts for pepper commodity, (ii) two sub-districts are very superior for cattle, one sub-district is very superior for buffalo cattle, three sub-districts are very superior for horse cattle, four subdistricts are very superior for goat livestock, six sub-districts are very superior for chicken farms , three sub-districts are very superior for layer chicken, four sub-districts are very superior for broilers and two sub-districts are very superior for duck livestock. The analysis of locality results for the estate crops sub-sector commodity showed that no sub-district had a locality coefficient value greater than or equal to one, for livestock populations there were no sub-districts that had a locality coefficient of greater than or equal to one.